Anisotropic response of the co-crystal of CL-20/TNT under shock loading: molecular dynamics simulation. Issue 61 (29th November 2021) - Li, Yan; Yu, Wen-Li; Huang, Huang; Zhu, Min; Wang, Jin-Tao
Abstract : Anisotropic response of the co-crystal of CL-20/TNT under shock loading is studied by analyzing the changes of thermodynamic parameters, product evolution and cluster evolution. Abstract : Using the molecular dynamics method based on the ReaxFF force field and combining it with the multi-scale shock technique, the physical and chemical change processes of CL-20/TNT co-crystals under shock loading were studied. Shock waves with velocities of 7, 8, 9 km s −1 were applied to CL-20/TNT co-crystals along the X, Y, and Z directions. The anisotropy brought by the co-crystal structure was analyzed. The results show that the temperature, stress, volume compressibility, decomposition rate, products, and the cluster of CL-20/TNT are strongly related to the direction of shock waves. With the same velocity, the shock wave along the Y direction can make the system more compressed, to obtain higher temperature and greater stress. When the velocities of shock waves are 7 km s −1 and 8 km s −1, systems with a higher degree of compression have a higher degree of chemical reaction, the reactants decompose faster, and richer products are generated. When the shock wave velocity is 9 km s −1, the chemical reactions are more intense, and the differences between reactants and products due to anisotropy are small. The amounts, compositions, sizes, and mass ratios of the cluster are strongly anisotropic due to the special layered structure of the energetic co-crystal, and the evolutionary processes are closely related to the chemical reaction process. The research in this paper can provide certain support for the understanding of the shock response process of energetic co-crystals.